William Howard Guest Rees. (10th February 2018) - Meldrum, Keith; Watson, Bill
Abstract : A distinguished vet who became the UK's chief veterinary officer, dealing with issues such as salmonella in eggs and bovine spongiform encephalopathy. His passions were his family and rugby.